2019
DOI: 10.1111/bph.14778
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and health status: Active ingredients and pharmacological mechanisms

Abstract: The Mediterranean diet (MedDiet) is one of the most widely described and evaluated dietary patterns in scientific literature. It is characterized by high intakes of vegetables, legumes, fruits, nuts, grains, fish, seafood, extra virgin olive oil, and a moderate intake of red wine. A large body of observational and experimental evidence suggests that higher adherence to the MedDiet is associated with lower risk of mortality, cardiovascular disease, metabolic disease, and cancer. Current mechanisms underlying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
187
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(204 citation statements)
references
References 156 publications
(219 reference statements)
2
187
0
15
Order By: Relevance
“…Numerous epidemiological studies have demonstrated the relationship between high consumption of whole grains (90 g or three servings per day) and the reduced risk of coronary artery disease, cardiovascular disease, total cancer, and all-cause mortality [42]. Similarly, the suboptimal intake of whole grains (38 g/d) was associated with CRC burden across 16 European countries [43]. Therefore, an optimal intake of 50-100 g/d was considered in our study to establish the dose administered in the AOM/DSS-induced CRC mouse model (75 g/d).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have demonstrated the relationship between high consumption of whole grains (90 g or three servings per day) and the reduced risk of coronary artery disease, cardiovascular disease, total cancer, and all-cause mortality [42]. Similarly, the suboptimal intake of whole grains (38 g/d) was associated with CRC burden across 16 European countries [43]. Therefore, an optimal intake of 50-100 g/d was considered in our study to establish the dose administered in the AOM/DSS-induced CRC mouse model (75 g/d).…”
Section: Discussionmentioning
confidence: 99%
“…Covalent inhibitors, such as 4‐chloro‐7‐nitro‐1,2,3‐benzoxadiazole (NBD‐Cl), modify the amino acid residues near the nucleotide‐binding site in the catalytic β subunits, while noncovalent inhibitors inhibit enzyme catalysis through weak interactions and do not directly interact with the catalytic sites. Noncovalent inhibitors, namely piceatannol, resveratrol, and quercetin, were selected among polyphenolic phytochemicals that abundantly occur in the Mediterranean diet and are known as beneficial in the treatment and prevention of human pathologies, such as cancer and cardiovascular diseases . These polyphenolic compounds are known to inhibit ATP hydrolysis by F 1 without binding to the catalytic sites by interacting with the enzyme in a common binding region on F 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A large section in this edition is devoted to un‐picking the benefits of the Mediterranean diet and the “French Paradox,” whereby moderate consumption of red wine, in the presence of fruits and vegetables, olive oil, some cheese and limited red meat is robustly associated with longevity and lower levels of all‐cause mortality including heart disease, type 2 diabetes, cancer and cognitive dysfunction. The review by Schwingshackl, Morze and Hoffmann () explores components within the Mediterranean diet thought most likely to endow benefits, providing informative schematics of the potential networks of biochemical changes underpinning the effects. The main challenge in this setting has been to define appropriate comparator diets.…”
mentioning
confidence: 99%
“…Schwingshackl et al () introduce the discussion of the therapeutic benefits of resveratrol, a phytoalexin from the polyphenol grouping found in red wine, which has achieved particular interest and where the depth of research is greater (Durazzo et al, ). This agent is explored in more detail in another article of this themed issue (Cheng et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation